Impact of acute intoxication on quantitative pupillometry assessment in the emergency department. Issue 5 (26th October 2022) - Jolkovsky, Eliana L.; Fernandez‐Penny, Felix E.; Alexis, Maya; Benson, Lauren N.; Wang, Bo Hwan; Abella, Benjamin S.
Abstract: Study Hypothesis/Objective: This prospective cohort study aimed to assess whether and to what extent different quantitative pupillometry (QP) metrics are associated with different intoxicant drug classes as well as investigate the potential benefit of QP as a tool in the rapid assessment of clinically intoxicated patients in the emergency department (ED). Methods: Between February 25, 2019 and April 24, 2021, 325 patients were enrolled in the EDs of the Hospital of the University of Pennsylvania (HUP) and Penn Presbyterian Medical Center (PPMC). Patients deemed clinically intoxicated or in withdrawal by an attending emergency physician were considered for eligibility. Patients <18 years old, with a chief complaint indicative of head trauma or stroke or without a urine drug screen (UDS) positive for drugs of abuse were excluded. QP data were also collected from a cohort of 82 healthy control subjects. Results: Neurological Pupil index (NPi) values did not vary significantly between control and study groups nor between study group patients with a UDS positive for opioids. With exception of latency of constriction, all other QP metrics for the study group were depressed relative to controls ( P < 0.005). Conclusions: This work demonstrated the feasibility of QP measurement in the ED, finding that NPi remains unaffected by clinical intoxication and therefore can potentially be used for ED patient evaluation without risk of confounding by key intoxicants of abuse. Future work will evaluate the value of QP as a means of rapid and reproducible neurological assessment to identify various pathologies.